Le passif de l’autorité - Margarita Rouski (Corela)
This article aims to provide some details about the function of passive structures used as marks of authority in legal texts. The passives that reorganize the relations between different participants in the process, receive in turn new interpretations in specific contexts. The legal communication as a human and social practice, is a legitimate part of a language dynamics. While aiming at absolute objectiveness of the rules of behavior, authority allows the legal norm to impose itself by indicating concrete outcomes. This tendency justifies the very frequent omission of the agent, made possible by the passive constructions. The anonymity of the agent and the objectification of the process which are part of the objective of the authority, lend at the pragmatic level, a prescriptive value to passive forms.